Identifying agricultural landscape types for Brandenburg, Germany using IACS data - Saskia Wolff; Silke Hüttel; Claas Nendel; Tobia Lakes (Humboldt-Universität zu Berlin, DFG Research Unit 2569 FORLand "Agricultural Land Markets - Efficiency and Regulation", 2020)
The increasing demand for agricultural commodities for food and energy purposes has led to intensified agricultural production. This trend may manifest in agricultural compositions and landscape configurations that can have mixed and adverse impacts on the provision of ecosystem services. We rely on the EU's plot-based data from the Integrated Administration and Control System (IACS) to identify different types of agricultural landscapes and their spatial distribution in Brandenburg, Germany, a study region strongly characterised by intensification trends. Based on a set of landscape metrics, we are able to characterise agricultural land use and identify six types of agricultural landscapes. We rely on a two-step cluster analysis for a hexagonal grid and find that agricultural land is dominated by cropland with different degrees of fragmentation. By providing a framework using landscape metrics derived from IACS data, our approach involves clustering to identify typologies that are transferable to other regions within the EU based on existing data. This framework can offer more tailored environmental and agricultural planning based on sophisticated measures that take into account local and regional characteristics.
urn:nbn:de:kobv:11-110-18452/22082-8
Keywords: R14; Q15; 330; agricultural land use; landscape metrics; cluster analysis; sustainable land use; land use